2016
DOI: 10.1016/j.ebiom.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis Between Flaviviruses Reveals Specific Neural Stem Cell Tropism for Zika Virus in the Mouse Developing Neocortex

Abstract: The recent Zika outbreak in South America and French Polynesia was associated with an epidemic of microcephaly, a disease characterized by a reduced size of the cerebral cortex. Other members of the Flavivirus genus, including West Nile virus (WNV), can cause encephalitis but were not demonstrated to cause microcephaly. It remains unclear whether Zika virus (ZIKV) and other flaviviruses may infect different cell populations in the developing neocortex and lead to distinct developmental defects. Here, we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 35 publications
(46 reference statements)
6
63
0
Order By: Relevance
“…Our finding that radial glia are preferentially infected during early neurogenesis is consistent with experiments in cultured primary human brain cells (19), developing mouse cortex (3,20), and primary human organotypic brain slice culture (7). These studies also reported overall survival of infected radial glia, in contrast to in vitro derived neural stem cells that undergo apoptotic cell death following infection (4,5,21).…”
Section: Discussionsupporting
confidence: 78%
“…Our finding that radial glia are preferentially infected during early neurogenesis is consistent with experiments in cultured primary human brain cells (19), developing mouse cortex (3,20), and primary human organotypic brain slice culture (7). These studies also reported overall survival of infected radial glia, in contrast to in vitro derived neural stem cells that undergo apoptotic cell death following infection (4,5,21).…”
Section: Discussionsupporting
confidence: 78%
“…Induction of caspase 3 cleavage occurred mostly within the cells that surround the virus-infected cell (Fig. 3), which has also been suggested by the results of other studies (30,31). These regions of apoptosis were confined to areas marked by ZIKV-E staining, as seen in the neocortex of an organotypic slice infected with the Malaysian isolate (Fig.…”
Section: Resultssupporting
confidence: 61%
“…2C). Poliovirus was used as a negative control, as the related flavivirus dengue was previously shown not to replicate in embryonic brain slices (30). Poliovirus did not replicate in brain slice cultures, as the mice used do not produce the poliovirus receptor, CD155 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, these genetic syndromes are often associated with a reduction in number of neuroprogenitor cells. Zika virus appears to behave in much the same way 5,6 , by targeting for infection those cells most vulnerable for injury, and whose numbers cannot be replaced.…”
mentioning
confidence: 99%